MicroRNA-27a (miR-27a) in Solid Tumors: A Review Based on Mechanisms and Clinical Observations - Zhang, Jingcheng; Cao, Zhe; Yang, Gang; You, Lei; Zhang, Taiping; Zhao, Yupei (Frontiers in Oncology, 2019)
MicroRNAs (miRNAs) are a family of highly conserved, non-coding single-stranded RNAs transcribed as 70 nucleotide precursors to an 18–22 nucleotide product (1). miRNAs can silence their homologous target genes at the post-transcriptional level, and these genes have been revealed to play an important role in tumorigenesis, invasion and metastasis (2). MicroRNA-27a (miR-27a), transcripted by miR-27a gene, has proved to implicate with many kinds of solid tumors, showing potential as a useful biomarker or drug target for clinical application. However, even though miR-27a has been reported in many cancers, the mechanism and signal pathways of miR-27 in oncogenesis, invasion, and metastasis are still obscure. Moreover, recent studies show that miR-27a pays an important role in epithelial-mesenchymal-transition, regulating tumor immune response, and chemoresistance. In this review, we summarize the current literature, demonstrate the established link between miR-27a and tumorigenesis, and focus on recently identified mechanisms. The review also aims to demonstrate the potential of miR-27a as a diagnostic and/or prognostic biomarker in solid tumors and to discuss the possibilities of targeted therapy and drug design.